Improvement in the Outcomes of MELD ≥ 40 Liver Transplantation: An Analysis of 207 Consecutive Transplants in a Highly Competitive DSA. Issue 10 (October 2017) - Nekrasov, Victor; Matsuoka, Lea; Kaur, Navpreet; Pita, Alejandro; Whang, Gilbert; Cao, Shu; Groshen, Susan; Alexopoulos, Sophoclis
Abstract : Background: Organ donor shortages continue to persist, especially in regions of the United States where competition is highest and recipients frequently attain a Model for End-Stage Liver Disease (MELD) score of 40 or higher before transplantation. The benefits of Share 35 in highly competitive regions may be underestimated when examining the collective national experience. The purpose of this study was to examine the outcomes of liver transplantation in recipients with a MELD of 40 or higher after implementation of Share 35 in a single center located in region 5. Methods: The method used in this study was single-center retrospective analysis of 207 liver transplant recipients who achieved MELD score of 40 or higher from April 21, 2002, to May 15, 2015. Results: Multivariable analysis identified implementation of Share 35 as the strongest predictor of graft survival in MELD of 40 or higher liver transplantation. The post–Share 35, 1-year graft survival was 94% compared with 75% pre–Share 35 ( P = 0.002). Post–Share 35 recipients waited significantly less time until transplantation (10 vs 16 days, P = 0.015), and fewer were hospitalized for more than 28 days before their transplant (6% vs 18%, P = 0.05). Multivariable analysis identified recipients with diabetes at the time of listing as the strongest predictor of posttransplant patient mortality. Conclusions: Implementation of the Share 35 allocation policy has a significant effect on outcomes by improving organ access and minimizing candidate waiting times. Recipients achieving a MELD of 40 or higher at our center post–Share 35 had an improved 1-year graft survival. However, nearly 40% remained hospitalized for more than 4 weeks posttransplant, and 20% were discharged to an acute care facility. Abstract : The authors analyzed their center's experience with the transplantation of patients with MELD score greater than 40. They were able to achieve a 94% graft survival in this cohort, which was improved from the era prior to Share 35. They propose that greater access to organs contributed to earlier transplant and better results although length-of-stay and resource consumption are high.